GEOINFORMATION SUPPORT FOR DEMINING THE TERRITORIES OF THE KHARKIV REGION - Myronenko, M.; Nesterenko, S.; Rai, A.; Frolov, O. (Municipal economy of cities. Series: «Economy science», 2024)
Modern conflicts and military actions result in massive landmine laying, making them dangerous for civilians. After the completion of hostilities, there is an urgent need to clear these areas to restore human life and infrastructure. The article presents the application of geographic information systems (GIS) and databases for the inventory and management of explosive ordnance data in post-conflict areas using the example of the Kharkiv region. The paper explains the structure and functioning of the explosive ordnance database, designed to optimise the demining process and increase its efficiency and safety. The explosive object database receives information from various sources, including mobile groups of the State Emergency Service of Ukraine, the National Police, and other units. The primary tool for fixing the coordinates of explosive objects is GPS devices. The database contains information about the coordinates of unexploded ordnance, their type, condition, date of discovery, the group that discovered it, and other information. The database allows searching and filtering of explosive objects by various criteria, generating reports on the number and types of explosives found in different areas of the region. Also, it is possible to visualise the data from the database on maps to enhance understanding of the distribution of explosive objects. Using the database can significantly improve the planning and coordination of demining work, track the progress of demining, assess the resources required for demining, warn the civilian population about the danger, analyse risks, conduct statistical analysis, report to the authorities, and train sappers. Implementing such a database will allow optimising demining planning, increasing the safety of sappers, and accelerating the restoration of a safe life for the population. The technology’s adaptability also means it can be utilised in other post-conflict regions, highlighting its potential for broader application. This system underscores the importance of integrating modern technological solutions in addressing the challenges of post-conflict reconstruction and safety.